2011
DOI: 10.1111/j.1756-1051.2011.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic reinstatement of Teucrium andrusi from T. paederotoides based on morphological and anatomical evidences

Abstract: Teucrium andrusi, described by Post from Mardin province, Turkey, was synonimized with T. paederotoides in the flora of Turkey. According to the records in the flora of Turkey T. paederotoides was a steno‐endemic species, only known from the type locality in Gaziantep and from Mardin province. Specimens of T. paederotoides s.l. were collected from both localities and a detailed comparison of the plants from Gaziantep with those from Mardin revealed that the two populations were sufficiently distinct from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…in Teucrium sect. Isotriodon (Dinç et al 2011a). But, this study showed that the studied taxa generally exhibit anatomical homogeneity with regard to stem and leaf anatomy (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in Teucrium sect. Isotriodon (Dinç et al 2011a). But, this study showed that the studied taxa generally exhibit anatomical homogeneity with regard to stem and leaf anatomy (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve species and two subspecies are endemic (Duman 2000;Dönmez 2006;Özhatay & Kültür 2006;Parolly & Eren 2007;Dönmez et al 2010;Dinç et al 2011a). Sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teucrium is a large and polymorphic genus which is represented by 49 taxa (36 species) in Turkey. There are 18 endemic taxa (Govaerts 1999, Duman 2000, Dönmez 2006, Parolly and Eren 2007, Dönmez et al 2010, Dinç et al 2011a, 2011b, Dirmenci 2012, Özcan et al 2015a, Vural et al 2015, Dinç and Doğu 2016). The classification of Teucrium is based on sections.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on Teucrium anatomy (Lakusic et al 2006, 2010, Dinç et al 2008, 2009, 2011a, 2011b, Dehshiri and Azadbakht 2012, Dinç and Doğu 2012, Doğu et al 2013, Özcan 2013, Özcan and Eminagaoglu 2014, Ruiters et al 2016). However, the anatomy of T. pestalozzae , T. brevifolium and T. alyssifolium has not been investigated.…”
Section: Introductionmentioning
confidence: 99%